Economic assessment for vegetable waste valorization through the biogas-biomethane chain in Italy with a circular economy approach - Bentivoglio, Deborah; Chiaraluce, Giulia; Finco, Adele (Frontiers in Sustainable Food Systems, 2022)
The current geo-political framework and the environmental concern about pollution and global warming are leading Europe to rethink its energy production, moving forward to the incentivization the renewable energy market. In this scenario, the use of waste from the agri-food sector shows a huge potentiality to enhance the transition in line with the circular economy principles. Biogas production represents an environmental friendly strategy to successfully recover large amounts of waste and by-products to produce renewable energy. Furthermore, in light of the rising need of green biofuels, biogas can be converted into biomethane, allowing the implementation of a full circular model. The objective of this paper is to perform an economic assessment to evaluate whether the upgrading of an existing biogas plant, in which the diet includes also vegetable waste from a plant producing frozen vegetables, could be profitable considering different scenarios, to reach a sustainable circular model. The analysis will be conducted through the Discounted Cash Flow method, considering four main indexes: NPV, DPBT, IRR, and PI. The results highlight the unprofitability of the biogas-biomethane chain if the upgrading system is performed maintaining the same characteristics of the starting plant. On the other hand, if changes in the digester's diet occur, the investment becomes immediately profitable in the considered time-span. The circular economy model is not completely accomplished, as profitability can only be reached if silage maize is partially kept as feedstock. Moreover, the conversion of the plant is not economically feasible if an adequate subsidy is not provided. The economic assessment of the upgrading system for biogas to biomethane is an essential element to be provided to the agribusiness entrepreneurs, as they need all the relevant economic aspects to decide to invest and adopt this solution to establish an innovative circular business model in agriculture.